Synthesis of 3-Thia-1-dethiacephems via Regioselective Iodocyclization Reaction - Garud, Dinesh R.; Rode, Navnath D.; Bathe, Sagar R.; Ranpise, Vinod S.; Joshi, Ramesh A.; Joshi, Rohini R.; Koketsu, Mamoru (Synthesis-Stuttgart, 2015)
The key N-homopropargylthiourea intermediates, N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides, were prepared by the reaction of a 4-propargylazetidin-2-one with isothiocyanates. Bicyclic -lactams, i.e. 3-thia-1-dethiacephems, were prepared via highly regioselective iodocyclization reaction of N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides with molecular iodine at room temperature in moderate to excellent yields. A variety of functional groups were well tolerated under the reaction conditions.
Keywords: -lactams; 3-thia-1-dethiacephems; Iodocyclization; Regioselective; thiourea